Actualization of the Bali Traditional Court in the Era of Society 5.0 - Sudjana, Made (International Asia Of Law and Money Laundering, 2024)
Bali local culture wisdom as an icon for Bali be well known in the world. Even, maybe, more known than Indonesia the country. This local wisdom needs to be maintained sustainable, and to be properly protected against other foreign cultures which introducing inferior values. In the present Society Era 5.0, the local wisdom needs to anticipate and accommodate changes such as Digitalization development. This writing describes about what factors and methodology of digitalization process specifically for : “Re-actualization of Bali custom court in society era 5.0”. The are many Custom Village cases in Bali. A riset conducted by Prof. Dr. Windia, in 2000 – 2004, there were 76 conflict cases wich 21 conflict Custom Village. In Kingdom Era, The Duch Colonialization until Independe Era. The custom village cases were handel by Village Judge, Village Court and Kertha Desa. Rule of Village Court like Kertha Desa up and down until the Independen Era due to intervention by government. In the Independen Era until the present day, Village Cases mostly handle by State Court, but the State Court decition not provide benefit to people. That reason why custom village court need to be reactualization in Society Era 5.0. In Neceserry in the Society Era 5.0 to review the challenges and the strategy to overcome those challengs. One of the challenges is digitalization ileterasi of court administration as well as the people them self. It need massive Digitalization Education. For the success of digitalization education requirement for appropriate equipment such as : Handphone, Computer Etc, should be completed as well as the qualified facilitators. The implementation of digitalization is socialized throught custom village organization, travel agencies, local imigran, etc. Concrecate digitalization in the form of copies of all religion and custom regulation such as : Awig-Awig, lontar- lontar (ancient teaching written in coconut leaves). For comparison, in Thailand, custom village cases initality handel by Pratama Court at village level. If not finalized then go to State Court. (Source : Kun Ibrahim). Different with in Malaysia and Singapura, all village cases directly handel by Police and process to State Court.